Mobile Legends: The World of Money-Making Games-What Drives Gamers to Buy Virtual Items in Online Games? - Andreas Ginting, Mario; Rusdiono, Rusdiono; Fitria Respati, Moudy; Helmi Situmorang, Syafrizal (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Research Objectives to determine how sales promotion and macro influencers affect purchasing decisions for virtual items in mobile legends online games with consumer satisfaction as a media variable. Research Methods Quantitative analysis, the population in this study were Mobile Legends players at the match held in Kabanjahe with the sample size being 100 people. This research analysis uses SEM-PLS with instrument tests to test validity and reliability and associative tests to test the influence between variables. The results of the study Sales Promotion (X1) have a significant and dominant influence on purchasing decisions. A good promotional strategy has proven effective in encouraging consumers to make purchases. Macro Influencer (X2) does not have a significant impact on buying decisions. This shows that the existence of macro influencers does not necessarily directly influence consumer decisions to buy. Consumer Satisfaction (Z) plays a very important role in influencing purchasing decisions. Customer satisfaction is proven to be a key factor that significantly determines purchasing decisions. Overall, the research model has excellent predictive ability, with an R-squared value of 0.826, which means that 82.6% of the variance in purchasing decisions can be explained by the variables in the model. Moderation Variables, the interaction between sales promotion variables or macro influencers with customer satisfaction does not have a significant moderating effect on purchasing decisions.